Efficacy of single low-dose dexamethasone with NEPA for the 168 h prevention of highly or moderately emetogenic chemotherapy - He, Yuting; Lou, Fanzhuoran; Huang, XinTian; Zhang, Yiqin; Lin, Qunbo; Tan, Weijuan; Chen, Quan; Ren, Xiurong; Shi, Huibo; Xiao, Li (Frontiers in Pharmacology, 2025)
BackgroundDexamethasone (DEX) can cause various side effects, particularly when used over several consecutive days to prevent chemotherapy-induced nausea and vomiting (CINV). Efforts to minimize the dose and frequency of DEX present challenges in managing CINV.MethodsThis single-center, retrospective study included 100 patients with solid tumors undergoing moderately emetogenic chemotherapy (MEC) or highly emetogenic chemotherapy (HEC). Each patient received a single low-dose DEX (8 mg) and NEPA prior to each chemotherapy cycle. The primary efficacy endpoint was the complete response (CR: no emesis, no rescue medication) within 0–168 h post-chemotherapy initiation in cycle 1. The main secondary endpoints were CR during the acute (0–24 h), delayed (24–120 h), and long-delayed (120–168 h) phases.ResultsBetween August 2023 and April 2024, a total of 100 patients received 230 chemotherapy cycles, consisting of 67.4% MEC and 32.6% HEC. CR rates rose from 85% in cycle 1–93.1% in cycle 4, with a slight decline during the delayed phase compared to the acute phase. Better outcomes appeared to be associated with fewer risk factors. Treatment was well-tolerated, with only Grade 1 or 2 adverse events reported; constipation and hyperglycemia were the most common. Regression analysis indicated a significant association between diabetes and CR rates (OR 0.09, 95% CI 0.02–0.40, p = 0.002).ConclusionSingle low-dose DEX (8 mg) with NEPA safely prevents CINV in high-risk patients during MEC/HEC cycles, offering an alternative to minimize the dose and frequency of DEX.